(untitled) (Theatrum historiae, 2014)
The study deals with the topic of the community oral history projects. It describes the Czech community local oral history project the Living History of Ratenice its methodology and outcomes. The author summarizes the historical development of oral history with the special attention to the community history in the first chapters. He also discusses the main methodological issues of this kind of projects. The following part is dedicated to the development of the project the Living History of Ratenice and its methodology. Then the article presents the project outcomes on the three selected topics – the historical changes of landscape and public space, the working life and finally the life during the Second World War.